1999
DOI: 10.1046/j.1365-2702.1999.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

The psychological consequences of source isolation: a review of the literature

Abstract: Source isolation can be an extremely frightening and anxiety provoking experience. With the many epidemiological changes that are prevalent in the UK today the need to care for individuals in source isolation is becoming increasingly important to prevent the spread of infection in hospitals. However, the psychological effects of source isolation are not well understood or researched. This review defines and examines the historical developments of source isolation and then discusses related research which sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 32 publications
4
42
0
Order By: Relevance
“…489,492,494,495 Children suggested that access to the Internet, mobile phones, and interactive resources and being able to leave their rooms would make isolation more tolerable. 489 Physical facilities can also be altered to decrease the impact of isolation.…”
Section: Studies Among Non-cf Patientsmentioning
confidence: 99%
“…489,492,494,495 Children suggested that access to the Internet, mobile phones, and interactive resources and being able to leave their rooms would make isolation more tolerable. 489 Physical facilities can also be altered to decrease the impact of isolation.…”
Section: Studies Among Non-cf Patientsmentioning
confidence: 99%
“…Recent studies have indicated that quarantine during the SARS outbreak was an emotional and, for some, a financial hardship (Blendon, Benson, DesRoches, Raleigh, & Taylor‐Clark, 2004; Hawryluck et al, 2004). Although some researchers have investigated the psychological consequences of hospital isolation practices (Gammon, 1999; Lesko, Kern, & Hawkins, 1984), little is known about the subjective experience of quarantine, for example, how people manage protocols and the supports or barriers to compliance. We therefore undertook a descriptive, qualitative study to explore the experience of being quarantined, specifically the relationship between perceived risk of contracting SARS and reported compliance with the quarantine order and protocols.…”
mentioning
confidence: 99%
“…Recommendations included parents' rooming in, the provision of play equipment, and the training of health care professionals specifically to educate and support hospitalized children (Bradley, 2001). Taken together, findings from child development research, along with new knowledge regarding how to control the spread of infection, resulted in changes to hospital visiting policies (Alsop-Shields & Mohay, 2001;Gammon, 1999).…”
mentioning
confidence: 99%